2017
DOI: 10.1073/pnas.1620208114
|View full text |Cite
|
Sign up to set email alerts
|

MRG15-mediated tethering of PALB2 to unperturbed chromatin protects active genes from genotoxic stress

Abstract: The partner and localiser of BRCA2 (PALB2) plays important roles in the maintenance of genome integrity and protection against cancer. Although PALB2 is commonly described as a repair factor recruited to sites of DNA breaks, recent studies provide evidence that PALB2 also associates with unperturbed chromatin. Here, we investigated the previously poorly described role of chromatin-associated PALB2 in undamaged cells. We found that PALB2 associates with active genes through its major binding partner, MRG15, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 53 publications
9
72
0
Order By: Relevance
“…So far, our analyses showed that ChAM acetylation promotes PALB2 association with nucleosomes/chromatin ( Fig. 6A), whereas PALB2 dissociates from active genes upon CPT treatment (Bleuyard et al, 2017b). These observations prompted us to further investigate whether ChAM acetylation is dynamically controlled during the DDR.…”
Section: Dna Damage Triggers Cham Deacetylation and An Increase In Pamentioning
confidence: 76%
See 4 more Smart Citations
“…So far, our analyses showed that ChAM acetylation promotes PALB2 association with nucleosomes/chromatin ( Fig. 6A), whereas PALB2 dissociates from active genes upon CPT treatment (Bleuyard et al, 2017b). These observations prompted us to further investigate whether ChAM acetylation is dynamically controlled during the DDR.…”
Section: Dna Damage Triggers Cham Deacetylation and An Increase In Pamentioning
confidence: 76%
“…Moreover, PALB2 intrinsic chromatin association is reinforced by the chromatin-association motif (ChAM), an evolutionarily conserved domain uniquely found in PALB2 orthologues, which directly binds to nucleosomes (Bleuyard et al, 2012). Notably, our locus-specific chromatin immunoprecipitation (ChIP) analyses revealed a decrease in PALB2 association with active genes following an exposure to a topoisomerase inhibitor camptothecin (CPT), suggesting that the mode of PALB2 chromatin association is actively regulated (Bleuyard et al, 2017b). Despite these observations, the regulatory mechanism by which PALB2 is switched between different modes of chromatin association (i.e.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations